Pengaruh Edukasi Pajak Terhadap Peningkatan Pengetahuan Wajib Pajak Orang Pribadi Melalui E-filing (Studi pada KP2KP Kabupaten Soppeng) - Fitri Rahmasari; Nugraha Abhull Azwad (Journal Axegnal: Tax And Economic Insights Journal, 2026)
This study aims to analyze the effect of tax education on increasing the knowledge of individual taxpayers through e-filing at the KP2KP office of Soppeng Regency. This study uses a quantitative method with data collection techniques by distributing questionnaires to 100 respondents to obtain data from taxpayers at the Tax Counseling and Consultation Service Office of Soppeng Regency. This study contributes to the development of taxpayer knowledge through e-filing. The results of this study indicate that tax education has a positive and significant effect on increasing the knowledge of individual taxpayers through e-filing. Tax education acts as an information bridge to help taxpayers understand their digital-based tax obligations. Education carried out by KP2KP Soppeng Regency is either through direct socialization, seminars or social media. proven to be able to increase taxpayers' knowledge in understanding electronic reporting procedures, replacing the previous manual system. Tax education also has a greater impact in the context of digitizing the tax system to make it easier and in accordance with modern regulations. This education is seen as an important factor in preparing taxpayers to understand and be able to use tax reporting services independently and correctly.